Development of Traffic Maze Media to Stimulate Problem of 4-5 Years Old Children - Nur Aliyah; Imam Tabroni; Cai Jixiong; Zhang Wei (Journal of Computer Science Advancements, 2023)
This study aims to produce a valid Traffic Maze learning media to improve the fine motor skills of children aged 4-5 years. This research is a development research with the development model used by Sugiyono. In this study, researchers only used 7 (seven) stages, namely knowing problems and potential, data collection, product design, design validation, design revision, product trials and product manufacturing. The next stage was not carried out due to cost and time constraints. The data collection technique used is a questionnaire, where the questionnaire is validated by material experts, media experts and educators. The type of data generated is quantitative and qualitative data. The average percentage result of the pretest conducted on 3 children is 12.3%, proving that the child's condition is still in the stage of starting to develop. Then the posttest is carried out, namely the condition after the child is given the Traffic Maze media, the average percentage result of this posttest is 31% which proves that the child has changed the condition to develop as expected. So it can be concluded that Traffic Maze media to improve the problem solving ability of children aged 4-5 years has met the criteria for validity.